Abdominal aortic aneurysm clinical practice guidelines: a methodological assessment using the AGREE II instrument. Issue 1 (20th January 2022) - Tan, Kia Hau Matthew; Salim, Safa; Machin, Matthew; Geroult, Aurélien; Onida, Sarah; Lane, Tristan; Davies, A H
Abstract : Objectives: Abdominal aortic aneurysm (AAA) clinical practice guidelines (CPGs) provide evidence-based information on patient management; however, methodological differences exist in the development of CPGs. This study examines the methodological quality of AAA CPGs using a validated assessment tool. Methods: Medline, EMBASE and online CPG databases were searched from 1946 to 31 October 2021. Full-text, English language, evidence-based AAA CPGs were included. Consensus-based CPGs, summaries of CPGs or CPGs which were only available on purchase were excluded. Five reviewers assessed their quality using the Appraisal of Guidelines for Research and Evaluation II instrument. An overall guideline assessment scaled score of ≥80% was considered as the threshold to recommend CPG use in clinical practice. Results: Seven CPGs were identified. Scores showed good inter-reviewer reliability (intraclass correlation coefficient 0.943, 95% CI 0.915 to 0.964). On average, CPGs performed adequately with mean scaled scores of over 50% in all domains. However, between CPGs, significant methodological heterogeneity was observed in all domains. Four CPGs scored ≥80% (European Society of Cardiology, the Society of Vascular Surgery, the European Society of Vascular Surgery and the National Institute of Health and Care Excellence), supporting their use in clinical practice. Conclusions: Four CPGs were considered of adequate methodological quality to recommend their use in clinical practice; nonetheless, these still showed areas for improvement, potentially through performing economic analysis and trial application of recommendations. A structured approach employing validated CPG creation tools should be used to improve rigour of AAA CPGs. Future work should also evaluate recommendation accuracy using validated appraisal tools.